A Pregnancy Case of Primary Mediastinal Large B Cell Lymphoma with Superior Vena Cava Syndrome - Lauren Brownhalls; Ann Gillett; Yasmin Whately; Keisuke Tanaka (Hindawi Limited, 2021)
Primary mediastinal large B cell lymphoma (PMLBCL) is a subtype of non-Hodgkin's lymphoma which presents rarely in pregnancy. It is an aggressive tumour that is associated with symptoms of superior vena cava (SVC) compression and airway compromise such as dyspnoea, facial and arm swelling, cough, or chest pain. Timely diagnosis is imperative to optimising patient outcomes and reducing both maternal and fetal morbidity and mortality. We report a case of a 33-year-old woman diagnosed with PMLBCL who presented at 33-week gestation with SVC obstruction to 1 mm in diameter. After multidisciplinary team discussion regarding maternal and fetal implications of management options, we proceeded to a caesarean section and initiated chemotherapy postdelivery. Lower segment caesarean section was uncomplicated, and she underwent a cycle of R-CHOEP followed by 5 cycles of DA-EPOCH. Eighteen months since the completion of the chemotherapy, the disease remained in remission.